2019
DOI: 10.1111/ajt.15133
|View full text |Cite
|
Sign up to set email alerts
|

Effect of recipient gender and donor-specific antibodies on antibody-mediated rejection after heart transplantation

Abstract: Gender‐difference regarding antibody‐mediated rejection (AMR) after heart transplantation has been described. However, no study accounted for the presence of preformed donor‐specific antibodies (pfDSA), a known risk factor of AMR, more common among women than men. In a single‐institution 6‐year cohort (2010‐2015), time to AMR was assessed, comparing men with women by survival analysis with a 1‐year death‐censored follow‐up. All AMRs were biopsy proven. Confounding variables that were accounted for included mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 22 publications
0
13
1
Order By: Relevance
“…The association between sex and having anti-HLA antibodies has been previously reported [27][28][29][30] . Gladstone et al 30 retrospectively reviewed 957 donors to evaluate the incidence of anti-HLA antibodies and DSAs and found that the incidence of anti-HLA antibodies was higher among females than males (43.2 versus 10.8%, P < 0.0001), and DSAs were most commonly detected in female patients (30.6% versus 4.9%, P < 0.00001) among candidates for haplo-SCT.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The association between sex and having anti-HLA antibodies has been previously reported [27][28][29][30] . Gladstone et al 30 retrospectively reviewed 957 donors to evaluate the incidence of anti-HLA antibodies and DSAs and found that the incidence of anti-HLA antibodies was higher among females than males (43.2 versus 10.8%, P < 0.0001), and DSAs were most commonly detected in female patients (30.6% versus 4.9%, P < 0.00001) among candidates for haplo-SCT.…”
Section: Discussionmentioning
confidence: 74%
“…Furthermore, Hyun et al 28 concluded that female solid organ transplantation candidates had a significantly higher PRA-positivity rate compared with that of male patients (60.3% vs 34.2%; P < 0.001). Nguyen et al 29 also found that women were at a higher risk of antibody-mediated rejection than men, and this increased risk was additive to that of preformed donor-specific antibodies after heart transplantation. Therefore, sex can be regarded as a specific risk factor for having anti-HLA antibodies and could guide their detection before SCT.…”
Section: Discussionmentioning
confidence: 96%
“…As previously described, the presence of DSAs at the time of transplant is an independent risk factor of rejection and mortality; therefore, patients in this cohort may have been at higher risk of rejection and mortality than nonimmunized patients, which may have increase the observed treatment-effect. 11,12 This may contribute to the observed improvement in survival of patients receiving quadritherapy compared with those receiving tritherapy, as explained by the concomitant use of mTOR inhibitors with CNIs resulting in a simultaneous blockade of mTOR and calcineurin pathways with a more effective lymphocyte T inhibition than that of a single pathway. 22 Immunosuppression based on multiple pathway blockade comes in opposition to findings coming from the Tacrolimus in Combination, Tacrolimus Alone Compared (TICTAC) trial, a prospective, randomized, controlled, open-label trial comparing tacrolimus alone as maintenance immunosuppressive regimen with standard tritherapy associating MMF and tacrolimus (corticosteroids were weaned to cessation in both groups).…”
Section: Discussionmentioning
confidence: 99%
“…This work was a single‐center observational, retrospective study using a propensity score to match patients treated with quadritherapy with patients treated with tritherapy immunosuppressant regimen. Data were collected in the scope of the HEart trAnsplantation Registry of piTie‐Salpetriere University Hospital (HEARTS) registry (ClinicalTrials.gov identifier NCT03393793) 12 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation